Responsible agricultural mechanization innovation for the sustainable development of Nepal’s hillside farming system - Devkota, Rachana; Pant, Laxmi Prasad; Gartaula, Hom Nath; Patel, Kirit; Gauchan, Devendra; Hambly Odame, Helen; Thapa, Balaram; Raizada, Manish N. (MDPI, 2020)
Agricultural mechanization in developing countries has taken at least two contested innovation pathways—the “incumbent trajectory” that promotes industrial agriculture, and an “alternative pathway” that supports small-scale mechanization for sustainable development of hillside farming systems. Although both pathways can potentially reduce human and animal drudgery, the body of literature that assesses the sustainability impacts of these mechanization pathways in the local ecological, socio-economic, cultural, and historical contexts of hillside farms is either nonexistent or under-theorized. This paper addresses this missing literature by examining the case of Nepal’s first Agricultural Mechanization Promotion Policy 2014 (AMPP) using a conceptual framework of what will be defined as “responsible innovation”. The historical context of this assessment involves the incumbent trajectory of mechanization in the country since the late 1960s that neglected smallholder farms located in the hills and mountains and biased mechanization policy for flat areas only. Findings from this study suggest that the AMPP addressed issues for smallholder production, including gender inequality, exclusion of smallholder farmers, and biophysical challenges associated with hillside farming systems, but it remains unclear whether and how the policy promotes small-scale agricultural mechanization for sustainable development of agriculture in the hills and mountains of Nepal.